Jogos Olímpicos: espetáculo de entretenimento planetário - Minuzzi, Evelize Dorneles (2013)
The following research aimed to understand Olympic Games as a spectacle of entertainment, explicit in the dimension of the infrastructure, in the expectation for the performance of athletes, in the media coverage of the event, in the grounds of the State, and in the private interests in hosting the games, in the amount of the economic costs, in the examples of overcoming limits, and in the possibility of enhancing or undermining national pride. For such, a bibliographic research has been conducted from scientific domain material, primary both for data collection and to perform the analysis of the object of study; and documentary research, through the analysis of print media "Folha de Sao Paulo" especially in the period from 1991 to 2012. As for the interpretation procedure, content analysis has been employed. The topic questioning takes into consideration the changes in the theoretical concept of time and free time, as the increased supply of goods for the time use, amongst them the spectacle. The emergence, the invention, reinvention and installation of Olympic Games in contemporary capitalist society is situated in this study, seeking similarities between the Olympic Games and entertainment spectacle. In summary, we aimed to demonstrate that the Olympic Games are a unique example of the globalization of entertainment, a planetary phenomenon of ideological control of capitalist society, transformed into merchandise for the immediate satisfaction of the public, profitable for the entertainment industry and somehow structuring capitalist ideology